FAKTOR FAKTOR YANG MEMPENGARUHI URBANISASI DI SUMATRA BARAT - Febbi Wulandari (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2017)
The purpose of this research was to knowing: (1) the impact  of income on urbanization in west Sumatra. (2) the impact  of education level on urbanization in west Sumatra. (3) the impact  of health facilities and infrastructure on urbanization in west Sumatra. (4) the impact  of education facilities and infrastructure on urbanization in west Sumatra. (5) the impact  of income, education level, health facilities and infrastructure, education facilities and infrastructure together on urbanization in west Sumatra.The type of this research is descriptive and associative. The type of research data is secondary data. This research uses panel data that is using 19 districts / cities in West Sumatra, By using approach Fixed Effect Model (FEM).  The results of this study show that: 1) income has a positive and significant effect on on urbanization in west Sumatra, (2) education level has a positive and insignificant effect on urbanization in West Sumatra, (3) Health facilities and infrastructure has negative and insignificant effect on urbanization in West Sumatera, (4) Education facilities and infrastructure has positive and insignificant effect on urbanization in West Sumatera, (5) Income, education level, health facilities and infrastructure, and education infrastructure facilities together have a significant effect on urbanization in West Sumatra.